2016
DOI: 10.3389/fimmu.2016.00490
|View full text |Cite
|
Sign up to set email alerts
|

Immune Imbalances in Non-Alcoholic Fatty Liver Disease: From General Biomarkers and Neutrophils to Interleukin-17 Axis Activation and New Therapeutic Targets

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an increasing problem worldwide and is associated with negative outcomes such as cirrhosis, hepatocellular carcinoma, insulin resistance, diabetes, and cardiovascular events. Current evidence shows that the immune response has an important participation driving the initiation, maintenance, and progression of the disease. So, various immune imbalances, from cellular to cytokines levels, have been studied, either for better compression of the disease pathophysiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 161 publications
(252 reference statements)
4
62
0
2
Order By: Relevance
“…Obesity increases de novo lipogenesis, inducing hepatic steatosis and NAFLD [12]. Excessive lipid accumulation in the hepatic tissue obstructs the normal physiological function of hepatocytes, and induced insulin resistance, inflammation, and peroxidation can cause the development of chronic liver fibrosis and hepatic cancer [22,23]. Many studies have found that reducing lipid accumulation can decrease liver inflammation and fibrosis in NAFLD, even allowing for the possibility of a return to normal liver function and lipogenesis, (B) the Sirt-1/AMPK pathway, and (C) lipolysis-and β-oxidation-associated proteins detected by western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases de novo lipogenesis, inducing hepatic steatosis and NAFLD [12]. Excessive lipid accumulation in the hepatic tissue obstructs the normal physiological function of hepatocytes, and induced insulin resistance, inflammation, and peroxidation can cause the development of chronic liver fibrosis and hepatic cancer [22,23]. Many studies have found that reducing lipid accumulation can decrease liver inflammation and fibrosis in NAFLD, even allowing for the possibility of a return to normal liver function and lipogenesis, (B) the Sirt-1/AMPK pathway, and (C) lipolysis-and β-oxidation-associated proteins detected by western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic accumulation of neutrophils, macrophages, and CD4 1 T cells (e.g., T helper [Th]1 and Th17 subsets) correlates with NAFLD progression. (34,35) NOX2 regulates hepatic immune cell infiltration and immune cell cytokine production. (36) Notably, proinflammatory cytokines (e.g., IFN-c, TNF-a, IL-17A) are well-established modulators of NAFLD pathogenesis.…”
Section: Nox2 Modulates Hepatic Immune Cell Inflammatory Vigormentioning
confidence: 99%
“…Our group discovered that peripheral blood Th17 cells from HCC patients suppress CD8 + T-cell responses indicating that Th17 cells promote HCC [80]. Accumulation of Th17 cells in NAFLD liver has been repeatedly observed [81][82][83][84]. In patients, the progression from NAFLD to NASH is marked by an increase in intrahepatic Th17 cells [84].…”
Section: Th17 Cellsmentioning
confidence: 99%